Anatomical variants in the maxillary sinus in individuals from Guatemala. A study at CBCT. - Anayansi-Melgar Girón, Marlen Esther (2020)
Objective: To determine the most frequent anatomical variants of the maxillary sinus by evaluation using cone beam computed tomography (CBCT) in a Guatemalan population attending the DISA Radiological Center in the period 2013-2018. Materials and Methods: Descriptive cross-sectional study. 217 CBCT was performed in a total of 434 maxillary sinuses, determining the frequency of anatomical variants, the presence of pneumatization of the maxillary sinus and their classification and sinus septa in association with sex and the dental condition of the patient. Measurements were made by a trained and calibrated researcher, using Carestream CS 3D software. The Chisquare test was used to determine associations among variables (p<0.05). Results: The frequency of pneumatization of the maxillary sinus was 79.2%, with class II being the most prevalent with 53.5%. The distribution and frequency of intrasinusal septa was observed in 136 maxillary sinuses (31.3%). Incomplete septa appeared more frequently (18.4%), being in a coronal direction in 27.1%, and located in the middle region of the maxillary sinus floor in 14.5%. The formation of primary partitions was presented in 13.1% and with a single presentation in 28.4%. An association was found between the class of pneumatization and the sex of the patient and between the formation of primary septa and the dental condition of the patient (p<0.05). Conclusions: The most prevalent anatomical variants in the maxillary sinus are pneumatization of the sinus floor and the presence of sinus septa, which were more frequently observed in female patients with partially dentate conditions.